THE EFFECTIVENESS OF TEACHING POETRY WRITING USING KINETIC SHORT FILMS BY PUTRI TANJUNG IN GRADE X AT SMK PUI GEGESIK FOR THE ACADEMIC YEAR 2023/2024 - Nurindah, Siti; Efendi, Irfan; Fajri, Khoirul (Transpublika Publisher, 2024)
This study aims to determine the effectiveness of learning to write poetry using short film media Kinetik by Putri Tanjung in class X SMK PUI Gegesik. This type of research is Experimental Research using Quasi experimental design. The population in this study was class X SMK PUI Gegesik. The sample in this study were students of class X DKV 1 as an experimental class consisting of 32 students and class X DKV 3 as a control class consisting of 32 students. Data collected by written test technique, namely pre-test and post-test. It was shown that media of kinetic short film is used effectively in learning to write free poetry because of the significant difference between the control class and the experimental class; namely, learners who used Kinetic short film media with those who did not use it. It can be seen based on the t-test results of the Pre-test and post-test scores in the control class and experimental class conducted with the help of the SPSS program. The result of statistical calculation using t test of two independent samples (independent sample t test). The obtained statistic is 4.075, with t table: 1.670. Thus, t statistic > t table (4.075 > 1.670).